PENGARUH SUPPLIER COMMUNICATION TERHADAP CUSTOMER FIRM COST PADA PERUSAHAAN MANUFAKTUR - Sri Vandayuli Riorini (Universitas Trisakti, 2006)
A quality product starts from supplier as natural resources and human resources for manufacturer. Relationship between the seller and the buyer can give advantage for customer. Suppliers’s skill and ability to share information to the buying company as well as information exchange between supplier and buying company will affect cost for the buying company and will be beneficial for their future relationship. There are two types of cost that can be affected by the relationship between supplier and the buying company, namely: (1) acquisition cost and (2) operational cost. The objective of the research is to determine and to analyze the affect of supplier communication towards customer firm cost in manufacturer. Data collected from 200 buying organizations / manufacturers in Jakarta. For analyzing data, the research uses Structural Equation Modeling, statistical technic which enable test between one or several dependent varibles as well as one or several independent variables. The results indicate that: (1) the more often supplier communicate directly (face to face) or communicate in writing with buying company the lower acquisition cost and operational cost for the buying company, (2) it is determined that supplier's sales force is a skilled person who has the ability to explain the product sold thus the buying company has a complete understanding of the product and later will affect the selling process, acquisition cost as well as operational cost for the buying company.